IMPLEMENTATION OF THE BLOCK SYSTEM IN VOCATIONAL HIGH SCHOOLS (ATIKANOTO: Journal of Automotive Engineering Education, 2025)
This study aims to determine the implementation of the block system in the productive subject of manual transmission systems at SMK Assalaam Bandung. Specifically, this research analyzes the block system in terms of learning implementation time, facilities and infrastructure, and student learning outcomes. The research method used is descriptive quantitative with a Scriven's Summative evaluation approach. The research sample consisted of teachers and eleventh-grade students of the Light Vehicle Engineering department, selected through a saturated sampling technique. Data collection techniques included interviews, questionnaires, observations, and documentation. The results of the study indicate that the block system effectively increases the flexibility of learning time, with the majority of students feeling that the learning time is adequate to explore both theoretical and practical material. In terms of facilities and infrastructure, the facilities available at SMK Assalaam Bandung meet feasibility standards, supporting an intensive learning process. In the aspect of learning outcomes, the implementation of the block system generally shows an improvement in student scores in both theoretical and practical aspects, although some students experienced a decrease in scores, indicating the need for adjustments to more effective teaching methods. Thus, the implementation of the block system in the productive subject of manual transmission at SMK Assalaam Bandung has an overall positive impact on the learning process and student learning outcomes. Penelitian ini bertujuan untuk mengetahui penerapan sistem blok pada mata pelajaran produktif tentang sistem transmisi manual di SMK Assalaam Bandung. Secara khusus, penelitian ini menganalisis sistem blok ditinjau dari waktu pelaksanaan pembelajaran, sarana dan prasarana, serta hasil belajar peserta didik. Metode penelitian yang digunakan adalah deskriptif kuantitatif dengan pendekatan evaluasi Summative Scriven. Sampel penelitian terdiri dari guru dan peserta didik kelas XI Teknik Kendaraan Ringan yang diambil melalui teknik sampling jenuh. Teknik pengumpulan data menggunakan wawancara, angket, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa sistem blok efektif meningkatkan fleksibilitas waktu pembelajaran, di mana sebagian besar peserta didik merasa waktu pembelajaran cukup memadai untuk mendalami materi teori maupun praktikum. Dari segi sarana dan prasarana, fasilitas yang tersedia di SMK Assalaam Bandung memenuhi standar kelayakan, mendukung proses pembelajaran yang intensif. Dalam aspek hasil belajar, penerapan sistem blok secara umum menunjukkan peningkatan nilai peserta didik baik pada aspek teori maupun praktikum, meskipun beberapa siswa mengalami penurunan nilai yang mengindikasikan perlunya penyesuaian metode pengajaran yang lebih efektif. Dengan demikian, penerapan sistem blok pada mata pelajaran produktif transmisi manual di SMK Assalaam Bandung secara keseluruhan berdampak positif terhadap proses pembelajaran dan hasil belajar peserta didik.